SATELLITE MAWLAWI AND ITS LITERARY HERITAGE - Zohidova Durdona Lutfullayevna; Saidakbarova Saint Muhammadrahimovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article will talk about the life and creative path, literary heritage of the prolific creator of Uzbek literature of the second half of the 19th century and the beginning of the 20th century, satellite Mawlawi. It is based on the need to thoroughly study the personality and literary heritage of this creator, whose works have not been widely studied, from a scientific point of view.